Question
upstudy study bank question image url

Applications 3.1 Express the following as single trigonometry ratio: 3.1.1 \( \cos 2 x \cdot \cos 3 x-\sin 2 x \cdot \sin 3 x \) 3.1.2 \( \sin 2 x \cdot \cos x+\cos 2 x \cdot \sin x \) \( \qquad \) (3) 3.2.1 \( \sin 85^{\circ} \cdot \cos 25^{\circ}-\cos 85^{\circ} \cdot \sin 25^{\circ} \) \( \qquad \) \( \qquad \) \( \qquad \) 3.2.2 \( \cos 160^{\circ} \cdot \cos 10^{\circ}+\sin 160^{\circ} \cdot \sin 10^{\circ} \) (4) \( \qquad \) \( \qquad \) \( \qquad \) \( \qquad \)

Ask by Logan Mccarthy. in South Africa
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

3.1.1: cos 5x 3.1.2: sin 3x 3.2.1: sin 60° 3.2.2: cos 150°

Solution

We can use the well‐known angle addition and subtraction formulas to simplify the expressions. 1. For 3.1.1, we have:   cos 2x · cos 3x – sin 2x · sin 3x Recall that cos(A + B) = cos A · cos B – sin A · sin B. Thus, with A = 2x and B = 3x,   cos 2x · cos 3x – sin 2x · sin 3x = cos(2x + 3x) = cos 5x. 2. For 3.1.2, we have:   sin 2x · cos x + cos 2x · sin x Recall that sin(A + B) = sin A · cos B + cos A · sin B. Thus, with A = 2x and B = x,   sin 2x · cos x + cos 2x · sin x = sin(2x + x) = sin 3x. 3. For 3.2.1, we have:   sin 85° · cos 25° – cos 85° · sin 25° Again, using the sine subtraction formula: sin A · cos B – cos A · sin B = sin(A – B). Thus, with A = 85° and B = 25°,   sin 85° · cos 25° – cos 85° · sin 25° = sin(85° – 25°) = sin 60°. 4. For 3.2.2, we have:   cos 160° · cos 10° + sin 160° · sin 10° Recall the cosine subtraction formula: cos A · cos B + sin A · sin B = cos(A – B). Thus, with A = 160° and B = 10°,   cos 160° · cos 10° + sin 160° · sin 10° = cos(160° – 10°) = cos 150°. So the simplified results are: • 3.1.1: cos 5x • 3.1.2: sin 3x • 3.2.1: sin 60° • 3.2.2: cos 150°

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

When you see the expression \( \cos A \cdot \cos B - \sin A \cdot \sin B \), think of it as a cozy trigonometric little house that can be neatly packed up into \( \cos(A + B) \). So, in this case, \( \cos 2x \cdot \cos 3x - \sin 2x \cdot \sin 3x = \cos(2x + 3x) = \cos(5x) \). Now for that fun little gem \( \sin A \cdot \cos B + \cos A \cdot \sin B \)! This is the cozy duet of our trigonometric functions coming together, which you've probably guessed leads to \( \sin(A + B) \). So, wrapping this up, \( \sin 2x \cdot \cos x + \cos 2x \cdot \sin x = \sin(2x + x) = \sin(3x) \). And don't forget when you're dealing with specific angles like \( \sin 85^{\circ} \cdot \cos 25^{\circ} - \cos 85^{\circ} \cdot \sin 25^{\circ} \), you can simplify that to \( \sin(85^{\circ} - 25^{\circ}) = \sin(60^{\circ}) \). Similarly, \( \cos 160^{\circ} \cdot \cos 10^{\circ} + \sin 160^{\circ} \cdot \sin 10^{\circ} \) can be swiftly packaged as \( \cos(160^{\circ} - 10^{\circ}) = \cos(150^{\circ}) \). Easy-peasy!

Related Questions

Latest Trigonometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy